The lady's snowbound scandal - Belgado, Paulia (Harlequin historicals., 2024)
A spinster, a scrooge…and only one bed! American industrialist Elliot has a plan to ensure his sisters will marry well—find a London society wife to elevate the family name! What’s not part of his plan is falling for the shy spinster who has no intention of marrying at all…Lady Georgina believes Elliot to be a heartless scrooge! Still, she needs his help to save her beloved orphanage in time for Christmas. So, in exchange, she offers to help him find a respectable wife. But when they’re scandalously snowed in at a coaching inn, their simmering attraction has no place to hide…